Analysis of Students' Learning Difficulties in Understanding the Concept of Nervous System Material in Humans at MAS Hajijah Amalia Sari - Ikhwan Riyaldi; Almira Amir; Wilda Rizkiyahnur Nasution (Bioedunis Journal, 2026)
Learning difficulties are one of the problems that students often experience in the biology learning process, especially in abstract and complex materials such as the human nervous system. Less than optimal understanding of concepts can have an impact on low student learning outcomes and hinder the achievement of learning goals. This study aims to analyze students' learning difficulties in understanding the concept of nervous system material in humans at MAS Hajijah Amalia Sari for the 2024 academic year. This study uses a quantitative approach with the support of qualitative data. The subject of the study was 25 students in grade XI of MAS Hajijah Amalia Sari. Data collection techniques are carried out through concept comprehension tests, interviews, and documentation. The concept comprehension test is prepared based on seven indicators of concept comprehension, namely interpreting, giving examples, grouping, summarizing, drawing inferences, comparing, and explaining. The data obtained was analyzed descriptively to determine the level of students' understanding of concepts and the form of learning difficulties experienced. The results showed that the level of students' conceptual understanding of nervous system material was in the medium category with an overall average score of 60. Indicators provide examples and interpret are in the good category, while indicators summarize, draw inferences, compare, and explain are in the sufficient category and indicate a more dominant level of difficulty. Students' learning difficulties are influenced by various internal factors, such as low high-level thinking skills, uneven learning motivation, and differences in students' initial abilities. In addition, external factors such as limited learning media, practicum facilities, and learning methods that are still dominated by lectures also affect students' understanding of concepts. Based on these findings, improvement efforts are needed through the application of more innovative learning methods, the use of visual and audiovisual media, and student-centered learning to improve conceptual understanding and reduce students' learning difficulties in human nervous system materials.